A retrospective analysis of concurrent chemoradiation for squamous cell carcinoma of the anus in Johannesburg - Phemelo Tshoeu; Vinay Sharma; Paul Ruff (South African Journal of Oncology, 2023)
Background: Anal cancer is a major cause of mortality and morbidity in low- and middle-income countries (LMICs).